Mechanism of mesenchymal stem cells and exosomes in the treatment of age-related diseases - Li, Jia; Huang, Yuling; Sun, Haiyan; Yang, Lina (Frontiers in Immunology, 2023)
Mesenchymal stem cells (MSCs) from multiple tissues have the capability of multidirectional differentiation and self-renewal. Many reports indicated that MSCs exert curative effects on a variety of age-related diseases through regeneration and repair of aging cells and organs. However, as research has progressed, it has become clear that it is the MSCs derived exosomes (MSC-Exos) that may have a real role to play, and that they can be modified to achieve better therapeutic results, making them even more advantageous than MSCs for treating disease. This review generalizes the biological characteristics of MSCs and exosomes and their mechanisms in treating age-related diseases, for example, MSCs and their exosomes can treat age-related diseases through mechanisms such as oxidative stress (OS), Wnt/β-catenin signaling pathway, mitogen-activated protein kinases (MAPK) signaling pathway, and so on. In addition, current in vivo and in vitro trials are described, and ongoing clinical trials are discussed, as well as the prospects and challenges for the future use of exosomes in disease treatment. This review will provide references for using exosomes to treat age-related diseases.